Hadiths About Social Education In The Book of Riyadhus Shalihin - Nasir, Muhammad; Khalilurrahman; Amaliah, Gina (The International Journal of Education Management and Sociology, 2023)
Hadiths serve as the second source of guidance after the Qur'an. All human issues should be guided by the Qur'an and Hadiths. Hadiths discuss various topics, with education being a significant focus. Islam encourages social interaction among individuals. The implementation of noble character education is highly appropriate, as neighbors are considered close relatives who deserve special attention in terms of character. Neighbors should help one another and not underestimate acts of kindness from neighbors, which reflect social education. In the book of Riyadhush Shalihin, the discussion on social education is found in chapter 39, which contains 9 hadiths. The objectives of this article are: (1) To identify hadiths that discuss social education, (2) To understand the forms of social education in the book of Riyadhush Shalihin. This research uses content analysis and descriptive method. The research results explain that: (1) One of the topics discussed in Riyadhus Salihin is social education. Social education in Riyadhus Shalihin can be found in Chapter 39. In this chapter, there are nine hadiths, ranging from Hadith No. 303 to Hadith No. 311. (2) Riyadhus Salihin provides valuable guidance on social education through these hadiths, encouraging qualities such as compassion, tolerance, kindness, mutual assistance, and fostering familial bonds among neighbors.